Indicação para o uso da terra na bacia hidrográfica do rio salobra - serra da bodoquena, mato grosso do sul - Da Silva Neto, João Cândido André [UNESP] (My University, 2012)
The process of appropriation of nature in the Watershed of Salobra River has occurred many times so intense and in inappropriate areas, not respecting the physical and natural characteristics of this landscape. This process should be based on the capability of economic exploitation of natural resources and the resilience of this ecosystem. From this perspective, the objective was to map appropriate areas for each type of land use, according characteristics of the landscape, verifying that 64% of the study area have problems of soil conservation or are indicated for reforestation, and 36% of the area are indicated for use with pasture or farming crops of short cycles/seasonal.
Indication for the land use of the watershed in salobra river - Bodoquena plateau, mato grosso do sul state
Keywords: Appropriation of the nature; Geographic information system; Land use; agricultural land; exploitation; GIS; land use change; landscape structure; natural resource; nature conservation; reforestation; soil conservation; watershed; Bodoquena Plateau; Brazil; Mato Grosso do Sul; Salobra River